Permissive role of reduced inwardly-rectifying potassium current density in the automaticity of the guinea pig pulmonary vein myocardium - Yayoi Tsuneoka; Masahiko Irie; Yusuke Tanaka; Takahiko Sugimoto; Yuka Kobayashi; Taichi Kusakabe; Keisuke Kato; Shogo Hamaguchi; Iyuki Namekata; Hikaru Tanaka (Elsevier, 2017)
The electrophysiological properties underlying the automaticity of the guinea pig pulmonary vein myocardium were studied. About 30% of the isolated pulmonary vein tissue preparations showed spontaneous electrical activity, as shown by glass microelectrode recordings from their myocardial layer. The remaining quiescent preparations had a resting membrane potential less negative than that in the left atria. Blockade of the acetylcholine activated potassium current (IK-ACh) by tertiapin induced a depolarizing shift of the resting membrane potential and automatic electrical activity in the pulmonary vein, but not in the atria. The tertiapin-induced electrical activity, as well as the spontaneous activity, was inhibited by the application of carbachol or by chelation of intracellular Ca2+ by BAPTA. The isolated pulmonary vein cardiomyocytes had an IK-ACh density similar to that of the atrial cardiomyocytes, but a lower density of the inwardly-rectifying potassium current (IK1). Spontaneous Ca2+ transients were observed in about 30% of the isolated pulmonary vein cardiomyocytes, but not in atrial cardiomyocytes. The Ca2+ transients in the pulmonary vein cardiomyocytes were induced by tertiapin and inhibited by carbachol. These results indicate that the pulmonary vein cardiomyocytes have a reduced density of the inwardly-rectifying potassium current, which plays a permissive role in their intracellular Ca2+-dependent automaticity.